Pengungkapan Rahasia Bank (Bank Secrecy) Terhadap Pelaku Tindak Pidana Perbankan - Hutabarat, Rugun Romaida; Putri, Amanda Fitriani Eka; Syamila, Najma; Michellena; Puspita, Salsabillah Ayu (Universitas Muhammadiyah Ponorogo, 2025)
The banking sector is a crucial tool for driving the Indonesian economy, maintaining balance, progress, and unity within the national economy. Naturally, the banking sector requires regulations and elements that play a crucial role in optimal economic operation. Indonesia, a country governed by the rule of law, naturally has regulations regarding banking in its implementation. Banks, as financial service institutions, are expected to maintain the trust of the public who invest their funds in them, as stipulated in banking law. The principle of bank secrecy requires banks to maintain the confidentiality of their deposits and to help protect the interests of individual customers as a guarantee for the public who will place their trust in the bank and can entrust their funds to it. The strong commitment of banks to maintaining bank secrecy as financial service providers, coupled with the development and advancement of science and technology, has given rise to a problem where banks are often used as venues for criminal acts. In the process of resolving banking crimes, many parties, such as banks, play a significant role in assisting in resolving the problem. However, in practice, the process of resolving the problem remains incomplete due to a legal vacuum in disclosing bank secrecy to perpetrators of banking crimes. Referring to the research results, Singapore is included in the category of countries with a fairly high level of bank secrecy and has special banking regulations to help resolve banking crimes specifically, making it a comparison in this research analysis.